Acoustic and dielectric properties of 0–3 bismuth sodium titanate-bismuth potassium titanate-barium titanate/cement composites. Issue 4 (15th December 2015) - Potong, Ruamporn; Rianyoi, Rattiyakorn; Ngamjarurojana, Athipong; Chaipanich, Arnon
ABSTRACT: The lead-free piezoelectric ceramic-cement composites made from bismuth sodium titanate-bismuth potassium titanate-barium titanate (BNBK) ceramic particle and Portland cement (PC) are developed for smart structure applications. The acoustic and dielectric properties of composites were investigated. The 30–60 vol% gave the optimal BNBK content for an acoustic impedance match between 0–3 connectivity BNBK-PC composites and structure materials, i.e. concrete. Parallel, cube and series models were also compared to the dielectric measurement results and the experimental values were found to fit closest to that of the cube model. The dielectric properties of composites were also found to depend on the frequency tested.